Being creative during lockdown: The relationship between creative potential and COVID‐19‐related psychological distress in narcolepsy type 1. (18th August 2021) - D'Anselmo, Anita; Agnoli, Sergio; Filardi, Marco; Pizza, Fabio; Mastria, Serena; Corazza, Giovanni Emanuele; Plazzi, Giuseppe
Summary: The national lockdown imposed in several countries to counteract the coronavirus disease 2019 (COVID‐19) pandemic led to an unprecedented situation with serious effects on mental health of the general population and of subjects affected by heterogeneous diseases. Considering the positive association between narcoleptic symptoms and creativity, we aimed at exploring the psychological distress associated with COVID‐19 restrictions and its relationship with depressive symptoms and creativity in patients with narcolepsy type 1 (NT1). A total of 52 patients with NT1 and 50 healthy controls, who completed a previous study on creativity, were contacted during the first lockdown period to complete an online survey evaluating psychological distress related to the COVID‐19 outbreak, sleep quality, narcolepsy and depressive symptoms, and creative abilities. The patients with NT1 showed an improvement in subjective sleepiness while controls reported worsening of sleep quality during the lockdown. Depression and NT1 symptom severity proved significant predictors of COVID‐19‐related distress. Creative performance, namely generative fluency, turned out to be a favourable moderator in the relationship between depression and patients' distress, reducing the detrimental effect of depression on the patients' wellbeing. On the contrary, creative originality proved to be a disadvantageous moderator in the relationship between NT1 symptom severity and the distress associated with this traumatic event indicating a higher vulnerability to developing COVID‐19‐related distress, particularly evident in patients displaying higher originality. Overall, these results highlight a crucial role of creativity in patients with NT1, suggesting that creative potential could be used as a protective factor against the development of distress associated with the lockdown.